Pola Perundungan Di Asrama Pesantren X: Analisis Waktu, Jenis, Dan Lokasi - Hermawan Setiawan; Tin Budi Utami; Primi Artiningrum (Badan Riset dan Inovasi Nasional (BRIN), 2025)
Bullying is an aggressive behavior manifested through verbal or physical actions intended to harm, intimidate, or demean others. This study analyzes bullying patterns occurring in Pesantren X by examining the distribution of types, locations, and temporal patterns within the dormitory setting. The research employed a quantitative descriptive approach with a random sampling technique involving 50 respondents. The findings indicate that hitting is the most prevalent form of physical bullying, while insults represent the dominant form of verbal bullying. Spatial analysis reveals that dormitory rooms constitute the highest-risk areas for both physical and verbal bullying. Temporally, bullying incidents peak during midday (11:46–15:00) and evening hours (19:00–22:00). The relationship between location, type, and time shows that the highest frequency of incidents occurred in Room 4 on the 5th floor, with four cases of physical bullying at night (19:00–22:00), while verbal bullying concentrated in Room 1 on the 5th floor during midday (11:46–15:00) with two cases. These findings highlight the importance of strengthening supervision during midday rest periods and evening personal-time activities. Future research is encouraged to incorporate seniority structures, group interaction patterns, and socio-cultural dynamics within pesantren environments to support more comprehensive prevention strategies.